The physics of being jewish, or on cats and Jews - Ginsburg, Shai P. (AJS review, 2011)
The opening scene of Joel and Ethan Coen's A Serious Man has baffled many. What does an unsettling tale of an encounter with what may or may not be a dybbuk, set in the mid-nineteenth century in a Polish shtetl, and played out entirely in Yiddish, have to do with the story of a Jewish professor of physics and his family in suburban Minnesota in the summer of 1967, related in English? Is the scene to be viewed as a warm-up of sorts before the main attraction, akin, if you will, to the short-subject films—newsreels, animated cartoons, and live-action comedies and documentaries—that movie houses of old used to play before the main feature? If so, what is the significance of presenting an odd Yiddish scene to an American audience notorious for turning a cold shoulder to non-English-speaking cinema? Or is the scene to be viewed as a prologue to the movie? If so, in what sense could it be said to impart to the audience either the “state of suspense of the plot produced by the previous history” or, alternatively, the argument of the drama?